IMF Research Bulletin, September 2004. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 2004)
The IMF Research Bulletin, a quarterly publication, selectively summarizes research and analytical work done by various departments at the IMF, and also provides a listing of research documents and other research-related activities, including conferences and seminars. The Bulletin is intended to serve as a summary guide to research done at the IMF on various topics, and to provide a better perspective on the analytical underpinnings of the IMF's operational work.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet